2007
DOI: 10.1007/s10637-007-9045-8
|View full text |Cite
|
Sign up to set email alerts
|

Erlotinib and vinorelbine in advanced malignant solid tumors: a phase I study

Abstract: (1) The MTD was vinorelbine 25 mg/m2 day 1 and 8 with erlotinib 100 mg/day every 21 days. (2) The combination was associated with high rate of febrile neutropenia (25%). (3) Due to subsequent data demonstrating a lack of efficacy of erlotinib in combination with platinum doublets in advanced NSCLC, this combination has not been explored further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…Previous trials performed by our group and others have also showed apparent sensitization of the myeloid compartment by toceranib as evidenced by enhanced myelosuppression noted when toceranib is used in combination with CCNU and vinblastine . In human clinical trials, similar findings have been observed with the combination of cytotoxic agents and RTKIs including gefitinib/gemcitabine, gefitinib/vinorelbine, erlotinib/vinorelbine and vinca alkaloids/EGFR inhibitor combination protocols . One suggested mechanism for this increased haematologic toxicity is that the RTKIs, DOX and vinca alkaloids are all metabolized by CYP3A4 enzymes, resulting in prolonged systemic exposure to the active metabolites due to saturation of hepatic metabolism when these agents are combined .…”
Section: Discussionsupporting
confidence: 75%
“…Previous trials performed by our group and others have also showed apparent sensitization of the myeloid compartment by toceranib as evidenced by enhanced myelosuppression noted when toceranib is used in combination with CCNU and vinblastine . In human clinical trials, similar findings have been observed with the combination of cytotoxic agents and RTKIs including gefitinib/gemcitabine, gefitinib/vinorelbine, erlotinib/vinorelbine and vinca alkaloids/EGFR inhibitor combination protocols . One suggested mechanism for this increased haematologic toxicity is that the RTKIs, DOX and vinca alkaloids are all metabolized by CYP3A4 enzymes, resulting in prolonged systemic exposure to the active metabolites due to saturation of hepatic metabolism when these agents are combined .…”
Section: Discussionsupporting
confidence: 75%
“…Neutropenia was the main cause limiting delivery of treatment and requiring dose delays. These results are similar to those reported by Davies et al [11] in a phase I study of erlotinib and vinorelbine in advanced malignant solid tumours and by Scagliotti et al [12] when combining gefitinib with vinorelbine in a phase II study. Nevertheless, it can be noticed that neutropenia did not translate to a high incidence of severe toxicities, as only 2 patients experienced febrile neutropenia, and one patient experienced neutropenic infection.…”
Section: Discussionsupporting
confidence: 92%
“…The combination of erlotinib and vinorelbine administered intravenously in the conventional manner has previously been investigated in another phase I study by Davies et al [ 21 ]. They reported an MTD of vinorelbine 25 mg/m 2 administered intravenously on Days 1 and 8 with erlotinib 100 mg/day every 21 days [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of erlotinib and vinorelbine administered intravenously in the conventional manner has previously been investigated in another phase I study by Davies et al [ 21 ]. They reported an MTD of vinorelbine 25 mg/m 2 administered intravenously on Days 1 and 8 with erlotinib 100 mg/day every 21 days [ 21 ]. In contrast to the low incidence of haematological toxicities observed in the CSV group in our study, the investigators noted a high incidence of grade 3/4 neutropenia (50%) and febrile neutropenia (25%), which occurred in patients receiving intravenous vinorelbine 25 mg/m 2 with erlotinib 150 mg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation